The Design and Implementation of an Intelligent Sports Training System for College Students’ Mental Health Education - Fengxian Teng (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Unconsciously, mobile Internet information influences college students' sports behavior and awareness, although the exact consequences have not been widely studied. The majority of the extant research focuses on behavioral science and sports communication. Using past research as a foundation, this study investigates the impact of mobile Internet on college students' sports behavior and awareness. In particular, a static structural analysis was performed on an intervention event network for the effect of mobile Internet on college students' sports behavior and awareness. Then, using system event analysis, a well-established method in complex system research, the interaction link between distinct intervention events in the network was investigated in depth, and the composite degree of effect between them was calculated. The core logic and action mechanism of the event-based hierarchy model were then revealed using the integrated fuzzy-interpretative structural model. Finally, experiments confirmed that the proposed paradigm was successful.